2016
DOI: 10.1371/journal.pone.0165636
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of VEGFA Variants and Changes in VEGF Levels Underscores the Contribution of VEGF to Polycystic Ovary Syndrome

Abstract: BackgroundVascular endothelial growth factor (VEGF) contributes to the pathogenesis of polycystic ovary syndrome (PCOS), and genetic variations in VEGFA gene were suggested to contribute to VEGF secretion and PCOS.AimTo evaluate the association of altered VEGF levels, stemming from the presence of specific VEGFA variants, with altered risk of PCOS.Subjects and MethodsRetrospective case-control study, performed between 2012–2015. Study subjects comprised 382 women with PCOS, and 393 control subjects. ELISA meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
0
27
0
2
Order By: Relevance
“…VEGFɑ could promote estradiol synthesis and survival of GCs in buffalo . SNP analysis revealed that VEGFɑ was associated with PCOS in humans . These results indicate that CDK6 , FILIP1L , ACAT2 , CEBPD , and VEGFɑ all have important functions in ovaries.…”
Section: Discussionmentioning
confidence: 83%
“…VEGFɑ could promote estradiol synthesis and survival of GCs in buffalo . SNP analysis revealed that VEGFɑ was associated with PCOS in humans . These results indicate that CDK6 , FILIP1L , ACAT2 , CEBPD , and VEGFɑ all have important functions in ovaries.…”
Section: Discussionmentioning
confidence: 83%
“…Five case-control studies involving 895 women with PCOS and 907 controls were included to estimate the relationship between the VEGF +405G>C (rs2010963) polymorphism and PCOS risk (Almawi et al, 2016;Guruvaiah et al, 2014;Huang et al, 2019;Lee et al, 2008;Vural et al, 2009). Overall, the pooled analysis showed no significant association between +405G>C (rs2010963) and PCOS in five genetic models.…”
Section: Association Between the Vegf ±405g≥c (Rs2010963) Polymorphismentioning
confidence: 99%
“…Full texts of the remaining nine were obtained and studied, and two of them were further excluded because of the absence of genotypic data. In the end, seven studies with detailed genotypic data were included in the systemic review (Almawi et al, 2016;Ben Salem et al, 2016;Gomes et al, 2019;Guruvaiah et al, 2014;Huang et al, 2019;Lee et al, 2008;Vural et al, 2009). These selected studies involved 1100 patients with PCOS and 1141 control individuals.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results were not conclusive or consistent. Considering the vital role of VEGF gene in the development of PCOS, we conducted a timely meta-analysis including 11 SNPs [21][22][23][24][25][26][27][28][29] to derive a more comprehensive estimation of the association between VEGF gene polymorphisms and PCOS susceptibility to identify some significant biomarkers.…”
Section: Figure 1 Flowchart Illustrating the Search Strategy Used Tomentioning
confidence: 99%